Effects of dual polymer conditioning on sludge dewatering - Koray, Elif Fulya. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2006., 2006)
The sludge dewatering has been known as one of the most expensive and hard to handle processes in water/wastewater treatment. Alum sludges have been recognized as difficult to dewater due to the containing 40 per cent bound water, are often conditioned with polymers prior to dewatering. Dual conditioning leads to an improvement in the sludge dewaterability. In dual conditioning, the better dewaterability can be achieved by using same or less amount of polymer than that of single conditioning. Dual conditioning increase the solid content of the sludge cake, enhance the solids capture and so reduce the blinding of the filter media. Rheology is known a direct proportionality relationship between shear stress and shear rate. The conditioned sludges show a non-Newtonian behavior. The rheological measurements are very useful in understanding wastewater treatment performance. This study investigates the effect of dual conditioning on sludge dewaterability and the rheological behavior of the conditioned alum sludges. Based on the results of this study, dual conditioning leads to an improvement in the dewaterability of sludges. The best sludge dewaterability was obtained by adding anionic polymer first and cationic second.|Keywords : Dual conditioning, Sludge dewatering, Alum sludge, Polymer, Rheology
Keywords: Sewage sludge.; Polymers.; Rheology (Biology)